ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (Studi Kasus Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Adi Kusuma Setyaji, 12.05.52.0042; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2016)
The purpose of study is to examine and analyze the factors that affect the Dividend Payout Ratio on LQ 45 companies. The population of this research are companies included in the category LQ 45 in 2012-2014. The sampling technique is done by purposive sampling. Based on the results of the sampling Proposive obtained a sample of 119 companies. This study uses analysis techniques with multiple linear regression. The results of this study show that each variable has influence varies ie Cash Ratio positive effect was not significant to Dividend Payout Ratio, Return on Assets and Firm Size significant positive effect on Dividend Payout Ratio, while Debt to Equity Ratio significant negative effect on Dividend payout Ratio, Current Ratio while the significant negative effect on the Dividend payout Ratio. Keywords: Cash Ratio, Return On Asset, Debt To Equity Ratio, Firm Size, Current Ratio, Dividen Payout Ratio